Rapid discrimination of bacteria using a miniature mass spectrometer. Issue 5 (4th February 2016) - Pulliam, Christopher J.; Wei, Pu; Snyder, Dalton T.; Wang, Xiao; Ouyang, Zheng; Pielak, Rafal M.; Graham Cooks, R.
Abstract : Bacteria colonies were analyzed using paper spray ionization coupled with a portable mass spectrometer. Abstract : Bacteria colonies were analyzed using paper spray ionization coupled with a portable mass spectrometer. The spectra were averaged and processed using multivariate analysis to discriminate between different species of bacteria based on their unique phospholipid profiles. Full scan mass spectra and product ion MS/MS data were compared to those recorded using a benchtop linear ion trap mass spectrometer.